UPAYA HUKUM DALAM PENYELESAIAN SENGKETA PAJAK - Asriyani, Asriyani (Katalogis, 2017)
The research was set because there was which occasinally rise difference between perceptual interpretation of tax calculation, tax payer and tax officer, it happened because there was no mutual understanding in the perceptual interpretation of tax calculation. This becomes a trigger of the happening of tax disputes in the terms of tax payer proposing an objection on tax asessment letter toward the determine tax and when the objection declined then the tax payer purpose the law equal to the tax court in accordance with the 36 article (4) clause in the law number 14 2002 about tax court, tax payer are required to pay about 50 % of tax debt before purposing the law equal, with the result that to realize the law attempt in the arrangement of tax disputes and whether the law attempt function as a medium of legal protection.